Sodium Phosphate Rectal Enema as a Source of Phosphorus in Dialysate: Use in Hypophosphatemic Critically Ill Patients Undergoing Acute Dialysis - Shaheen Bibi; Mehwish Qamar; Fahad Naseem; Ahmed Kunwer Naveed; Sumbal Nasir Mahmood; Kunwer Naveed Mukhtar (Pakistan Journal of Medical Research, 2025)
Background: Phosphorus disorders, including hypophosphatemia and hyperphosphatemia, are common in critically ill patients with acute kidney injury and contribute to adverse outcomes. Standard dialysis solutions often exacerbate hypophosphatemia, necessitating innovative strategies like phosphorus-enriched dialysate for safer management.